Introducing urine-enriched biochar-based fertilizer for vegetable production: acceptability and results from rural Bangladesh - Ipsita Sutradhar; Meredith Jackson-deGraffenried; Sayema Akter; Shannon A. McMahon; Jillian L. Waid; Hans-Peter Schmidt; Amanda S. Wendt; Sabine Gabrysch (Environment, Development and Sustainability, 2021)
Improved agricultural practices that increase yields and preserve soils are critical to addressing food insecurity and undernutrition among smallholder farmer families. Urine-enriched biochar has been shown to be an accessible and effective fertilization option in various subtropical countries; however, it is new to Bangladesh. To better understand attitudes and experiences preparing and using urine-enriched biochar fertilizer, mixed-methods research was undertaken among smallholder farmers in northeastern Bangladesh in 2016/2017. In-depth interviews were conducted with 25 respondents who had compared the production of crops grown with biochar-based fertilizer to usual practice. In addition, in areas where trainings on biochar-based fertilization had been offered, 845 farmers were asked about their experience through a quantitative survey. Interview results indicated that cow urine-enriched biochar was favored over human urine because cow urine was perceived as clean and socially acceptable, whereas human urine was considered impure and disgusting. Respondents praised biochar-based fertilizer because it increased yields, cost little, was convenient to prepare with readily available natural materials, produced tastier crops, and allowed families to share their larger yields which in turn enhanced social and financial capital. Comparative field trials indicated a 60% yield benefit in both cabbage and kohlrabi crops. Challenges included uneven access to ingredients, with some respondents having difficulty procuring cow urine and biomass feedstock. The low social, health, and financial risk of adoption and the perceived benefits motivated farmers to produce and apply biochar-based fertilizer in their gardens, demonstrating strong potential for scale-up of this technology in Bangladesh.
Keywords: 330; Agricultural production; Family farms; Home gardening; Biochar; Urine; Bangladesh